Cognitive self-assessment scales in surgical settings: Acceptability and feasibility. Issue 3 (September 2018) - Stoicea, N.; Koehler, K.N.; Scharre, D.W.; Bergese, S.D.
Abstract : Pre-existing cognitive impairment is associated with poor surgical outcomes, long hospital stays, and increased morbidity and mortality. This necessitates the use of screening tools to evaluate preoperative cognitive status in elderly surgical patients. Given the growing population of older adults and increased prevalence of cognitive impairment, it is necessary to investigate whether staff-administered or self-administered cognitive screening examinations provide more sensitive information about pre-existing (preoperative) cognitive status. Self-administered Gerocognitive Screening Examination (SAGE) was developed out of the need for a cognitive self-assessment scale in the clinic. At our institution, SAGE was given to 189 elderly surgical patients to evaluate baseline cognitive status, and preliminary results are promising that self-assessment scales are both feasible and acceptable in the surgical setting.